Strategies for feeding the world more sustainably with organic agriculture - Radu Gheorghe Antohe; Nicolae Suvorov (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Global hunger and insufficient nutrient intake are worldwide debated issues. The present paper aims to identify the main problems in the agri-food sector and to find solutions for achieving sustainable food systems. Organic farming is proposed as a promising approach. A better understanding of the role that organic agriculture could play in the sustainable development of the food system, helps us to establish the environmental externalities related to the 100% conversion in organic agriculture. It needs more land than conventional agriculture but can drastically reduce the use of nitrogen and plant protection products. However, due to the problem of world hunger, food waste due to inappropriate consumer behaviour, but especially insufficient production, the global conversion to organic farming remains in the scenario stage. Another aspect that requires an interdisciplinary approach is the correlation between high-performance food systems that protect the environment and the interdependencies between crops, animals, and human consumption.
Keywords: Q1; Q18; Q19; 330; green economy; organic agriculture; hunger; sustainable development